Legal Certainty of Limited Partnership (CV) Registered In The District Court After The Enactment Of Minister Of Law And Human Rights Regulations Number 17 Of 2018 - Diman Ade Maulada; Arief Rahman (Unram Law Review, 2019)
The purpose of this research discusses the legal certainty of cv registered in the district court after the enactment of Minister of Law And Human Rights Regulations Number 17 Of 2018, the research method used is a normative research method. Normative legal research methods or library research methods are methods or methods used in legal research conducted by examining existing library materials. CVs registered at a district court prior to the enactment of the Minister of Law and Human Rights Regulation No. 17 of 2018 are legally valid because their establishment is based on provisions stipulated in the Commercial Code, thus providing legal certainty for the owner, with the obligation to record CV registration in the business organization application system (SABU).